Building Regional Innovation Network: Evidence from Koridor Economic of Sumatra - Ansofino Ansofino (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The focus of this research is how to interrelate regional innovation products with regional trade and the creation of economic agglomerations in the economic corridor of Sumatra. The research approach used is the spatial lag model and the spatial error model using 2020 spatial data in 10 provinces in the economic corridor of Sumatra. The results show that first: Innovation products and regional trade are spatial variables because they have a greater Moran index value, with the centre of the cluster being Riau province, areas around the centre of the cluster, such as North Sumatra, West Sumatra, South Sumatra. The increase in regional trade intensity is able to encourage an increase in innovation products in the Sumatra economic corridor. On the other hand, the increase in innovation products by large industries has not had a significant impact on increasing regional trade in the Sumatra economic corridor. Second: The factors that affect the increase in innovation products in large and medium industries in the economic corridor of Sumatra are the increase in added value in the beverage industry, increase in added value in the computer and electronic goods industry, and the creation of agglomerations in the food and beverage industry. Meanwhile, an increase in government spending on increasing R&D and venture capital encourages a decline in innovation products in large and medium industries in the Sumatra economic corridor. Third: The factors that affect the increase in regional trade in the economic corridor of Sumatra are increased government spending on R&D, increased added value in the beverage industry, increased added value in the computer and electronic equipment industry, and regional innovation products. Fourth: The cluster centre for increasing the added value of the computer industry and the beverage industry as a very important variable in increasing regional innovation products and regional trade in the long term is the province of Riau and Aceh and this greatly impacts the hinterland area.